Prognosis of Neonatal Asphyxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Of 86 asphyxiated full-term neonates with CNS complications admitted to the Intensive Care Unit at the Nagoya City University Hospital, Japan, during a 10 year period (1972-81), 63 (73%) survived the neonatal period.